The Effectiveness of The Five-Column Model In Acquiring Chemical Concepts Among Second-Grade Middle School Students (Journal of the College of Basic Education, 2025)
The research aims to identify the effectiveness of the five-pillar model in acquiring chemical concepts among second-grade intermediate female students. The researchers used the experimental design with partial control for two equivalent groups. The research sample was intentionally selected from second-grade intermediate female students from (Rayat Al-Huda Intermediate School for Girls). The number of students in the research sample was (67) students, with (34) students in the experimental group studying according to the five-pillar model and (33) students in the control group studying according to the traditional method. The researchers conducted statistical equivalence between the two research groups using variables (previous achievement scores for chemistry, Raven’s Intelligence Test, and previous information test). The scientific material was also determined, represented by (Chapter One: Elements and Chemical Bonding, Chapter Two: Chemical Compounds, and Chapter Three: Formulas and Chemical Reactions) scheduled to be taught for the academic year (2024-2025). The researchers formulated (143) behavioral objectives. The researchers prepared the research tool represented by the chemical concepts acquisition test for chemistry. Its paragraphs were formulated, which amounted to (60) objective test paragraphs of the multiple-choice type, and the validity of the tool was verified. After the researchers completed the application of the experiment, the tool was applied to the two research groups, and the students' answers were corrected and processed statistically using the statistical package SPSS24. The results showed the superiority of the students of the experimental group over the students of the control group. In light of the results, the researchers put forward a number of recommendations and proposals.